Antenna placement for landslide monitoring using Analytical Hierarchy Process (AHP) and Geographical Information System (GIS) - Mustafa I.S.; Din N.M.; Ismail A.; Omar R.C.; Khalid N.H.N. (IEEE Computer Society, 2023)
Landslide monitoring of Tenaga Nasional Berhad (TNB) transmission towers in the remote areas is a challenging process especially if the slope is at a mountainous terrain and suspected to be insecure and risky. One option is to do real time monitoring by deploying the appropriate sensors for slope failure detection such as inclinometer, rain gauge and piezometer. This study presents a monitoring network planning to determine the best possible antenna location for landslide monitoring. It is based on Analytic Hierarchy Process (AHP) as a multi criteria decision making procedure and the extensive use of Geographical Information System (GIS) data in arriving at consensus decision in selecting the best location for remote monitoring applications. 2013 IEEE.